Stimulus-Induced Rhythmic, Periodic, or Ictal Discharges in Coma—Incidence and Interrater Reliability of Continuous EEG After a Standard Stimulation Protocol: A Prospective Study. Issue 4 (July 2017) - Alsherbini, Khalid A.; Plancher, Joao Mc-O'Neil; Ficker, David M.; Foreman, Brandon P.; Adeoye, Opeolu M.; Ying, Jun; Privitera, Michael D.
Abstract : Purpose: Stimulus-induced rhythmic, periodic, or ictal discharges (SIRPIDs) are often seen during continuous electroencephalographic (cEEG) monitoring in coma. Given their uncertain clinical significance, our prospective study evaluated incidence of SIRPIDs in comatose patients in the neuroscience intensive care unit (NSICU) who underwent a standard stimulation protocol and defined interreader reliability for cEEG. Methods: Of 146 patients prospectively screened who underwent cEEG during a 6-month period, 53 patients were included and 93 patients were excluded. Our protocol used a sequence of auditory, mild tactile, and painful stimuli tested in a quiet room. Continuous electroencephalogram were then reviewed offline by blinded experts, with interrater agreement assessed by kappa statistic. By Pearson χ 2 and Wilcoxon rank-sum tests, we then compared binary and numerical clinical features between those with and without SIRPIDs. Results: Of 53 patients who underwent our protocol, one patient with a corrupt cEEG file was excluded. Traumatic brain injury was the most common diagnosis. Moderate interrater agreement was observed for 66 total stimulations: 20 patients (38.5%) had possible or definite SIRPIDs by minimum one reviewer. For 19 stimulations reviewed by a third reviewer, consensus was reached in 10 cases making the incidence of SIRPIDs 19.3% in our cohort. There was a moderate interrate agreement with kappa of 0.5 (95% confidence interval: 0.1, 0.7). Median intensive care unit stay was 15 days in patients with SIRPIDs versus 6.5 days in those without ( P = 0.021). Conclusions: Our prospective study of SIRPIDs in the neuroscience intensive care unit found a 19% incidence by cEEG using a standard stimulation protocol, most often rhythmic delta activity, and showed a moderate interrater agreement. Abstract : Supplemental Digital Content is Available in the Text.